Artificial Intelligence in Marketing & Sales : The ABB experience Subtitle: Building a model for technologically driven change management in a B2B multinational corporation - Edmundo, Ana; Brunet-Thornton, Richard; Jirsák, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
Artificial Intelligence is becoming commonplace. Innovative corporations independently of their size feel the pressure to implement, in their operations, artificial intelligence (AI) systems. Yet insufficient research on how to successfully implement such systems exists. This thesis proposes to fill this gap, answering how can AI be successfully driven, when global teams introduce the change and local teams face the change. The method followed was grounded theory research and the data collection counted with the live experience of 20 individuals from four perspectives: vendors, B2B corporations, consulting implementation partners, and Artificial Intelligence researchers. As a result, the Artificial Intelligence Life Cycle (AILC) framework emerges containing eleven consecutive steps. To understand the global and local interaction the framework is then applied in a tangible ABB case study. This exploratory study aids to reach a new level of understanding on AI by advising best-practices and harmonising the “plug and play” expectations of practitioners.
Vedoucí práce: Richard Brunet-Thornton
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses